A Review on Critical Edition of Ayurveda Manuscripts (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda is an ancient science dealing with health care. In the ancient period, the knowledge was passed down from mouth to ear in an oral tradition. Later on, the Acharyas began to record these knowledge by writing it down on different materials like palm leaves, birch bark, copper plates.etc. Thus, Ayurveda began to be codified through centuries in written documents called Manuscripts. India is rich in its collection of medical as well as other manuscripts. Most of these remain unpublished. As such, several unique disease conditions and medical formulations contained in these texts are being lost by decaying. Many versions of the same text can be obtained from different places and therefore different readings about the same subject are seen. Ayurveda being mostly presented in Sanskrit language, a slight difference in reading makes a lot of difference in the interpretation of its meaning. Critical edition of a manuscript deals with the analysis of various versions of a text, to find out which is more meaningful and closer to the original text. It conveys many unique ideas; clarify the existing confusions and misinterpretations. Thus critical edition of all Ayurveda manuscripts is necessary. In the recent times a lot of Ayurveda scholars are coming up with the aim of bringing out the knowledge hidden inside these manuscripts through their critical edition. The aim of this paper is to review the various steps involved in the critical edition of a manuscript through examples.